2021
DOI: 10.1186/s11658-021-00280-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum exosomal pregnancy zone protein as a promising biomarker in inflammatory bowel disease

Abstract: Background Inflammatory bowel disease (IBD) is a kind of intestinal immune dysfunction disease, and its occurrence and prevalence are on the rise worldwide. As a chronic gastrointestinal disease, its pathogenesis is still unknown. Exosomes are vesicles in various body fluids that carry a variety of substances. They can mediate intercellular communication and long-distance transport of multiple media. In this study, we investigated the protein profile of serum exosomes from healthy people and IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Finch found that PZP was released into neutrophil extracellular traps (NETs) and reported a novel link between airway infection ( 23 ). It had been reported that PZP of serum-derived exosomes in inflammatory bowel disease was higher than healthy people ( 24 ). Skornicka confirmed that PZP could selectively modulate T-cell activation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finch found that PZP was released into neutrophil extracellular traps (NETs) and reported a novel link between airway infection ( 23 ). It had been reported that PZP of serum-derived exosomes in inflammatory bowel disease was higher than healthy people ( 24 ). Skornicka confirmed that PZP could selectively modulate T-cell activation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most contributing factor in the prediction model is PZP. PZP is up-regulated in a number of different inflammatory conditions and may contribute to immune regulation by non-covalently sequestering a series of other ligands including TNF-alpha, IL-2 and IL-6 [ 26 , 27 ]. In our study, PZP was shown to be correlated with nCRT response and ypT stage.…”
Section: Discussionmentioning
confidence: 99%
“…PZP is a high-molecular-weight immunosuppressive glycoprotein that is elevated during pregnancy. The role of this protein as an autoimmunity mediator was established by a recent LC–MS/MS-based study in inflammatory bowel disease patients [ 26 ]. In this study, we also found increased expression of PZP in all the RA serotypes as compared to the controls using LC–MS/MS.…”
Section: Discussionmentioning
confidence: 99%